2023
DOI: 10.1590/1678-9199-jvatitd-2023-0039
|View full text |Cite
|
Sign up to set email alerts
|

Snake venom disintegrins update: insights about new findings

Gabriela de Oliveira Almeida,
Isadora Sousa de Oliveira,
Eliane Candiani Arantes
et al.

Abstract: Snake venom disintegrins are low molecular weight, non-enzymatic proteins rich in cysteine, present in the venom of snakes from the families Viperidae, Crotalidae, Atractaspididae, Elapidae, and Colubridae. This family of proteins originated in venom through the proteolytic processing of metalloproteinases (SVMPs), which, in turn, evolved from a gene encoding an A Disintegrin And Metalloprotease (ADAM) molecule. Disintegrins have a recognition motif for integrins in their structure, allowing interaction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 142 publications
(184 reference statements)
0
7
0
Order By: Relevance
“…Since D. russelii venom contains disintegrins and disintegrin-like proteins 30 , they may impact the migration of myoblasts. These proteins are rarely found in elapid venoms 31 and therefore, these venoms may not adversely affect integrins-mediated cell migration. Previous studies have reported that an SVMP from B. alternatus reduces the migration of myoblasts in culture through mechanisms dependent and independent of its protease activity 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Since D. russelii venom contains disintegrins and disintegrin-like proteins 30 , they may impact the migration of myoblasts. These proteins are rarely found in elapid venoms 31 and therefore, these venoms may not adversely affect integrins-mediated cell migration. Previous studies have reported that an SVMP from B. alternatus reduces the migration of myoblasts in culture through mechanisms dependent and independent of its protease activity 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this compound undergoes a chemical change that increases its affinity for platelet glycoproteins, especially GPIIb/IIIa receptors [ 32 ]. Therefore, this drug is able to prevent platelet aggregation and other thrombotic activities by competing with fibrinogen for the RGD domain recognition site in the GPIIb/IIIa receptor [ 98 , 99 , 100 ]. In 1998, the Food and Drug Administration (FDA) approved tirofiban as a therapeutic intervention for acute coronary syndrome [ 101 ].…”
Section: Utilization Of Svd As Pro-angiogenic Agentsmentioning
confidence: 99%
“…They are potent inhibitors of both platelet aggregation and integrin-dependent cell adhesion. Some SVMPs contain a disintegrin domain [41,42].…”
Section: Snake Venom Metalloproteinases (Svmps)mentioning
confidence: 99%